Empirical study on the usage of cash flow statement as a tool to predict company financial distress / Shariful Amran Abd Rahman - Abd Rahman, Shariful Amran (2001)
This study was carried out to examine whether cash flow can be a good predictor to debt restructuring companies. Sixty companies of Kuala Lumpur Stock Exchange (KLSE) have been identified as a sample in the current study. Thirty companies were classified as debt restructuring and another 30 matching companies were classified as non-debt restructuring companies. The classification was done in order to determine the differences between cash flow related ratios such as cash flow changes, cash flow over total debt, cash flow over total assets, cash flow over current liabilities and cash flow per share issued. The study hypothesized that the means for the cash flow based ratios have no significant difference between debt restructuring and non-debt restructuring companies. Based on trend analysis, there is no obvious pattern obtained from the graph plotted using average figure for each of the cash flow related ratios. Trend analysis and Mann- Whitney U test show that no significant difference exists between the means for debt restructuring and non-debt restructuring companies for all the cash flow related ratios. The results from stepwise logistic regression analysis further strengthen the hypothesis that the cash flow information does not have predictive power. Even though cash flow information has no predictive ability to forecast financial distress, it is useful for inter-company comparison.